2017
DOI: 10.18632/oncotarget.17379
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C deficiency suppresses tumor growth in a breast cancer model through decreased proliferation of tumor cells

Abstract: Cysteine cathepsins are proteases that, in addition to their important physiological functions, have been associated with multiple pathologies, including cancer. Cystatin C (CstC) is a major endogenous inhibitor that regulates the extracellular activity of cysteine cathepsins. We investigated the role of cystatin C in mammary cancer using CstC knockout mice and a mouse model of breast cancer induced by expression of the polyoma middle T oncoprotein (PyMT) in the mammary epithelium. We showed that the ablation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 88 publications
(93 reference statements)
0
11
0
1
Order By: Relevance
“…CTSZ belongs to the cathepsin family of lysosomal hydrolases that contribute to the turnover of intra cellular proteins and the degradation of extracellular matrix [ 25 ]. Interestingly, several of the tumor-promoting functions of CTSZ were not dependent on its described catalytic activity [ 26 ]. Several proteases have been shown to mediate adhesion and migration of cells through interaction with integrins [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTSZ belongs to the cathepsin family of lysosomal hydrolases that contribute to the turnover of intra cellular proteins and the degradation of extracellular matrix [ 25 ]. Interestingly, several of the tumor-promoting functions of CTSZ were not dependent on its described catalytic activity [ 26 ]. Several proteases have been shown to mediate adhesion and migration of cells through interaction with integrins [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several proteases have been shown to mediate adhesion and migration of cells through interaction with integrins [ 27 ]. CTSZ contains an Arg-Gly-Asp (RGD) motif allows it to interact with integrins [ 26 , 28 ]. RGD is a protein sequence vital to the binding of proteins to cell surface [ 29 ], which mediates cell adhesive properties, and this region interacts with the integrin αvb3 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first study revealed that genetic ablation of cystatin C, major extracellular cathepsin inhibitor, in the pancreatic neurocrine tumor model (Rip-Tag2) resulted in an increased size of islet cell carcinomas and angiogenic islets, which was linked to deregulated cathepsin S activity leading to increased endostatin generation [91]. The other two studies available included genetic ablation of stefin B, the major intracellular cathepsin inhibitor [131], and of cystatin C [132], in the mammary gland PyMT mouse model. However, contrary to all expectation, tumors were smaller in both inhibitor knock-out models despite the increased cathepsin activity in the tumors.…”
Section: Ecm Proteolysis and The Cathepsinsmentioning
confidence: 99%
“…Twenty visual fields per tumor section (20x magnification) in non-necrotic areas were quantified using ImageJ software (https:// imagej.nih.gov/ij/ ) and the Immunohistochemistry Image Analysis Toolbox. 6 , 38 , 39 …”
Section: Methodsmentioning
confidence: 99%